KEKUATAN HUKUM PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) SEBAGAI LEMBAGA SMALL CLAIM COURT DALAM PENYELESAIAN SENGKETA KONSUMEN - Mardika, Daniel; Putra Ariyana, I Gede (Kertha Semaya : Journal Ilmu Hukum, 2014)
This paper shall be entitled as “Legal Consequence of Consumer Dispute Settlement Body Decision as Small Claim Court in Dispute Settlement”. It shall apply the normative legal research method combined with the statutory approach. Within the circumstances the dispute arise, both consumer and entrepreneur might indict a lawsuit and be submitted towards the body. As one of the non-litigation body, it shall be authorized to perform judicial actions in order to settle small and simple lawsuit.
Keywords: Legal Consequence, Decision, Consumer Dispute Settlement Body, Small Claim Court